1986
DOI: 10.1161/01.cir.73.4.758
|View full text |Cite
|
Sign up to set email alerts
|

Subaortic stenosis, the univentricular heart, and banding of the pulmonary artery: an analysis of the courses of 43 patients with univentricular heart palliated by pulmonary artery banding.

Abstract: Subaortic stenosis is well known to complicate the clinical course of patients with single ventricle or univentricular hearts, and we have previously suggested that the development of subaortic stenosis in such patients may be causal to and/or accelerated by previous banding of the main pulmonary trunk. To further define the relationship between banding of the pulmonary artery in patients with univentricular hearts and the development of subaortic stenosis, we examined the morphologic substrate and timing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 43 publications
1
72
0
1
Order By: Relevance
“…This strategy can maintain acceptable anatomy and haemodynamics for later bidirectional Glenn and Fontan procedures [67,68]. However, PAB is implicated in the accelerated development of subaortic obstruction that ultimately jeopardised Fontan candidacy [67][68][69][70][71][72][73][74][75][76]. Other complications associated with a poorly positioned band or migrations are reported, including branch pulmonary stenoses, semilunar valve insufficiency, and erosion with aneurysm formation [67,69].…”
Section: Single Ventriclementioning
confidence: 99%
“…This strategy can maintain acceptable anatomy and haemodynamics for later bidirectional Glenn and Fontan procedures [67,68]. However, PAB is implicated in the accelerated development of subaortic obstruction that ultimately jeopardised Fontan candidacy [67][68][69][70][71][72][73][74][75][76]. Other complications associated with a poorly positioned band or migrations are reported, including branch pulmonary stenoses, semilunar valve insufficiency, and erosion with aneurysm formation [67,69].…”
Section: Single Ventriclementioning
confidence: 99%
“…Subsequent progression to a Fontan circulation is associated with a low postoperative mortality and good long-term clinical outcome. Importantly, none of the patients suffered postoperative heart block or needed reoperations for intracardiac obstruc- tions which have previously been highlighted as potential risks in this group of patients [2,9,10] In patients with TGA and a single left ventricle, the VSD is at risk of becoming restrictive. This may happen due to a natural tendency for this particular type of muscular VSD to become smaller, as supported by Rao [9].…”
Section: Discussionmentioning
confidence: 91%
“…Progression to a restrictive VSD may also be accelerated by surgical palliation: pulmonary artery banding may lead to myocardial hypertrophy and hence VSD restriction with subaortic obstruction [2,10]. Freedom et al reported in patients with single ventricle physiology and TGA initially palliated with pulmonary artery band a high incidence (84.4%) of developing subaortic obstruction [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmoner hipertansiyon ile birlikte koarktasyon veya kesintili arkus aorta sıklıkla eşlik eder. İki ventrikül arasındaki ilişkiyi sağlayan bulboventrikü-ler foramenin daralması ve subaortik obstrüksiyon gelişimi sık görülen komplikasyondur (1). Bu çalışmada Mart 2007 ile Mart 2010 arasında hastanemizde çift girişli sol ventrikül (DILV) ve ventriküloarteriyel diskordans tanısı alan hastalarımızı bulboventriküler foramende (BVF) restriksiyon gelişimi açısından değerlendirerek, tanı anında bu klinik seyri öngörebilecek değiş-kenleri incelemeyi amaçladık.…”
unclassified